2009
DOI: 10.1093/alcalc/agn115
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alcohol Advertising and Media Exposure on Adolescent Alcohol Use: A Systematic Review of Longitudinal Studies

Abstract: Longitudinal studies consistently suggest that exposure to media and commercial communications on alcohol is associated with the likelihood that adolescents will start to drink alcohol, and with increased drinking amongst baseline drinkers. Based on the strength of this association, the consistency of findings across numerous observational studies, temporality of exposure and drinking behaviours observed, dose-response relationships, as well as the theoretical plausibility regarding the impact of media exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
596
2
18

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 818 publications
(654 citation statements)
references
References 37 publications
26
596
2
18
Order By: Relevance
“…This can be seen in alcohol advertising research, which often posits a dose–response relationship whereby increased exposure to the advertising produced by multi‐national corporations generates increased harmful behaviour by directly influencing individual decision‐making, particularly among vulnerable populations 36. A practice perspective would argue instead that advertising situates products within practices and aims to develop, reinforce or evolve links between the materials, competences and meanings comprising those practices.…”
Section: Discussionmentioning
confidence: 99%
“…This can be seen in alcohol advertising research, which often posits a dose–response relationship whereby increased exposure to the advertising produced by multi‐national corporations generates increased harmful behaviour by directly influencing individual decision‐making, particularly among vulnerable populations 36. A practice perspective would argue instead that advertising situates products within practices and aims to develop, reinforce or evolve links between the materials, competences and meanings comprising those practices.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no direct endorsement of tobacco brands, their presence in music videos is arguably entirely unnecessary and illegal under the 2002 Act 50. In light of consistent evidence, including longitudinal studies, that exposure to tobacco 16, 18, 52 and alcohol 10, 11, 12, 13, 53 promotion and advertising encourages the uptake of smoking and alcohol use in adolescents, our concern is that young people will emulate these smoking and drinking behaviours and therefore that music videos containing alcohol and tobacco content should be restricted. Tobacco and alcohol marketing opportunities should be controlled more tightly in social and user‐generated media, and official music video makers and distributors should be proactive in working towards this goal.…”
Section: Discussionmentioning
confidence: 99%
“…There is now strong evidence that adolescent exposure to paid‐for advertising and other alcohol or tobacco media imagery in the media increase subsequent alcohol 10, 11, 12, 13, 14, 15 and tobacco use 16, 17, 18, 19, 20, 21. Media exposure includes films and television programmes, in which both tobacco 22, 23, 24, 25, 26 and alcohol 13, 26, 27, 28, 29, 30, 31 imagery are common.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that alcohol outlet density is associated with increased alcohol consumption and drinking problems or consequences, [13][14][15] and other studies have shown that alcohol advertising is associated with more positive attitudes regarding drinking, drinking initiation at younger ages, brand preference, and alcohol consumption. [16][17][18][19][20] Several studies have investigated the effects of neighborhood disadvantage on substance use, but findings have been mixed. 21 Some studies have found that neighborhood disadvantage is associated with increased alcohol consumption, heavy drinking, 22,23 and drinking consequences.…”
Section: Introductionmentioning
confidence: 99%